1992
DOI: 10.1093/oxfordjournals.eurheartj.a060226
|View full text |Cite
|
Sign up to set email alerts
|

Epidural spinal electrical stimulation for severe angina: a study of its effects on symptoms, exercise tolerance and degree of ischaemia

Abstract: The effectiveness of epidural spinal electrical stimulation has been studied in 14 patients with severe intractable angina unresponsive to standard therapies including bypass grafting. After implantation of the neurostimulator units the patients were assessed by a symptom questionnaire, treadmill exercise testing and right atrial pacing. There was a significant improvement of symptoms and GTN consumption fell markedly. With the neurostimulator on, exercise duration increased from a mean (CI) of 414 (153) to 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 0 publications
1
44
0
1
Order By: Relevance
“…This population of neurons provides rapid and timely reflex coordination of autonomic neuronal outflow to the heart (Armour, 1999). Clinical observations show that SCS reduces the magnitude of ST segment changes in the electrocardiogram (ECG) induced by exercise and rapid cardiac pacing (Sanderson et al, 1992). SCS is considered to improve cardiac function to a considerable degree by regulating the intrinsic cardiac nervous system .…”
Section: Intrinsic Cardiac Nervous System Related Mechanism-mentioning
confidence: 99%
“…This population of neurons provides rapid and timely reflex coordination of autonomic neuronal outflow to the heart (Armour, 1999). Clinical observations show that SCS reduces the magnitude of ST segment changes in the electrocardiogram (ECG) induced by exercise and rapid cardiac pacing (Sanderson et al, 1992). SCS is considered to improve cardiac function to a considerable degree by regulating the intrinsic cardiac nervous system .…”
Section: Intrinsic Cardiac Nervous System Related Mechanism-mentioning
confidence: 99%
“…Later, several observational and randomized studies, making use of this expertise to evaluate antiischemic effects of SCS, by means of bicycle or treadmill exercise stress tests as the method of choice, show consistent findings of a reduction in ST-T segment depression at maximal and at comparable work load, in conjunction with improvement in exercise duration. 57,59,61,62,63 So, in spite of a prolonged exercise duration the patients had less myocardial ischemia. However, in a meta-analysis of 5 randomized studies on exercise stress tests ST-T segment changes were not significantly altered, following SCS (Fig 4) Some studies included in the meta-analysis used a subthreshold versus threshold stimulation, others used the design of stimulation versus no stimulation and others used stimulation versus active non-neurostimulation comparators.…”
Section: Electrical Neuromodulation and Myocardial Ischemiamentioning
confidence: 90%
“…Since the first publications, abundant articles have testified that electrical neuromodulation gained credentials in efficacy as an adjuvant therapy for in patients with severe refractory angina, irrespective of whether the method is applied at the skin of the chest, 42,43 cervically 55 at the T1-4 thoracic level, 56,57 or subcutaneously. 52,55 To assess the efficacy of electrical neuromodulation among patients with refractory angina receiving the various forms of electrical neuromodulation, comparative randomized control studies are warranted.…”
Section: Electrical Neuromodulation and Anginamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have consistently reported a reduction of myocardial ischemia as measured by exercise test [1, 2, 3, 4], long-term ECG monitoring [5, 6], lactate metabolism [7]or stress echocardiography [8]. The Electrical Stimulation versus Coronary Artery Bypass Surgery (ESBY) Study [9]studied spinal cord stimulation as an alternative to coronary artery bypass grafting (CABG) in patients with no prognostic benefit from CABG and increased surgical risk.…”
Section: Introductionmentioning
confidence: 99%